Quiescence preconditioned nucleus pulposus stem cells alleviate intervertebral disc degeneration by enhancing cell survival via adaptive metabolism pattern in rats - Chen, Qi; Yang, Qu; Pan, Chongzhi; Ding, Rui; Wu, Tianlong; Cao, Jian; Wu, Hui; Zhao, Xiaokun; Li, Bin; Cheng, Xigao (Frontiers in Bioengineering and Biotechnology, 2023)
Quiescence is a cellular state of reversible growth arrest to maintain homeostasis and self-renewal. Entering quiescence allows cells to remain nondividing for extended periods of time and enact mechanisms to protect themselves from damage. Due to the extreme nutrient-deficient microenvironment in the intervertebral disc (IVD), the therapeutic effect of cell transplantation is limited. In this study, nucleus pulposus stem cells (NPSCs) were preconditioned into quiescence by serum starvation in vitro and transplanted to repair intervertebral disc degeneration (IDD). In vitro, we investigated apoptosis and survival of quiescent NPSCs in a glucose-free medium without fetal bovine serum. Non-preconditioned proliferating NPSCs were used as controls. In vivo, the cells were transplanted into a rat model of IDD induced by acupuncture and the intervertebral disc height, histological changes and extracellular matrix synthesis were observed. Finally, to elucidate the mechanisms underlying the quiescent state of NPSCs, the metabolic patterns of the cells were investigated through metabolomics. The results showed that quiescent NPSCs decreased apoptosis and increased cell survival compared to proliferating NPSCs in vitro and in vivo, and maintained the disc height and histological structure significantly better than proliferating NPSCs. Furthermore, quiescent NPSCs have generally down-regulated metabolism and reduced energy requirements in response to the switch to a nutrient-deficient environment. These findings support that quiescence preconditioning maintains the proliferation and biological function potential of NPSCs, increases cell survival under the extreme environment of IVD, and further alleviates IDD via adaptive metabolic patterns.